On correlated lotteries in economic applications - Dertwinkel-Kalt, Markus; Ebert, Sebastian; Köster, Mats (SSRN, 2022)
Economic models and experiments frequently use lotteries with only a few outcomes. We provide a comprehensive analysis of the correlation between such lotteries as well as their dependence structure more generally. We fully characterize the joint distribution of two binary lotteries via their first three univariate moments and their correlation coefficient. As we illustrate alongside some examples, the resulting parametrization may be useful for economic modeling and experimental design
Gesehen am 20.03.2023
Nach Informationen von SSRN wurde die ursprüngliche Fassung des Dokuments May 3, 2022 erstellt